La giurisdizione di legittimità e full jurisdiction. Le potenzialità del sindacato confutatorio - Follieri, Francesco (P.A. Persona e Amministrazione, 2018)
Secondo recenti studi sul concetto di ‘full jurisdiction’ nella giurisprudenza della Corte EDU sull’art. 6 della Convenzione, la full jurisdiction richiede che il giudice si sostituisca all’amministrazione, sia nella ricostruzione dei fatti (anche nei casi di c.d. “discrezionalità tecnica”), sia nella decisione circa la misura da adottare e il relativo assetto di interessi (la c.d. “discrezionalità amministrativa” o “discrezionalità pura”). In altre parole, secondo quest’interpretazione della giurisprudenza della Corte, la full jurisdiction coincide con il sindacato diretto o sostitutivo (permesso solo in giurisdizione di merito) e invece che con il sindacato indiretto o confutatorio (permesso in giurisdizione di legittimità). Di conseguenza, accogliendo tale tesi, i limiti imposti alla giurisdizione di legittimità dal diritto positivo sono incostituzionali per violazione dell’art. 117 Cost. Il presente lavoro discute questa tesi, mettendo in luce che nella giurisprudenza della Corte EDU «it is not the role of Article 6 of the Convention to give access to a level of jurisdiction which can substitute its opinion for that of the administrative authorities» (Sigma Radio Television ltd. v. Cyprus, §153). Nella giurisprudenza della Corte EDU, il sindacato confutatorio è sufficiente ad assicurare la full jurisdiction. In base all’art. 6 CEDU e all’art. 113 Cost., tuttavia, i giudici amministrativi non possono negare o limitare l’esercizio della loro giurisdizione su provvedimenti discrezionali o su questioni di c.d. discrezionalità tecnica, sostenendo che in quei casi il loro sindacato possa essere solo esterno o sia limitato al rilievo della manifesta irragionevolezza o travisamento dei fatti. Ai sensi dell’art. 6 CEDU e dell’art. 113 Cost., i giudici amministrativi devono ammettere qualunque confutazione avanzata dal ricorrente e alla stregua di queste confutazioni sindacare il provvedimento, quale che sia il provvedimento impugnato. According to some recent Italian studies on the concept of ‘full jurisdiction’ in the ECHR’s case-law on Article 6 of the Convention, the full jurisdiction requires the judge to substitute his opinion for that of the administrative authority, both over facts and the relevant evaluation (the so-called “technical discretion”) and the measure and the relevant balance of interest preferred by the administration (the “administrative discretion” or “pure discretion”). In other words, according to this interpretation of the Court’s case-law, the full jurisdiction is equal to the judicial review through substitution (forbidden under Italian Law, with the exception of certain matters, set forth by laws), instead of the judicial review through refutation (which is generally allowed in Italian legal system). As a consequence, according to this interpretation of the ECHR’s case-law, the limits imposed by Italian law to judicial review are unconstitutional, on the ground of breach of article 117 of Italian Constitution (which obliges the Italian legislator to comply with the obligations under international treaties – like the European Convention on Human Rights). The paper discusses this thesis, emphasizing that according to ECHR’s case-law «it is not the role of Article 6 of the Convention to give access to a level of jurisdiction which can substitute its opinion for that of the administrative authorities» (Sigma Radio Television ltd. v. Cyprus, §153). Under Article 6 of the Convention, the judicial review through refutation is a sufficient review. Under Article 6 of the Convention and Article 113 of the Italian Constitution, administrative judges cannot however deny or restrain their jurisdiction over discretionary acts or matters of “technical discretion”, claiming that in these cases their review is limited to “external review” or to patent unreasonableness or mistake in fact. Under Article 6 of the Convention and Article 113 of the Italian Constitution, the administrative judges shall admit any refutation by the applicant and review the administrative decision in the light of these refutations, whatever the challenged decision is. Parole chiave: full jurisdiction - modalità di sindacato - sindacato confutatorio - sindacato sostitutivo Keywords: full jurisdiction - judicial review - judicial review through refutation - judicial review through substitution